A study on knowledge, understanding and perception of state government staff towards the Government Transformation Programme (GTP) and Economic Transformation Programme (ETP) / Hamkhah Md Syukur and Mohammad Farid Ag Omar - Md Syukur, Hamkhah; Ag Omar, Mohammad Farid (2012)
The Government Transformation Programme (GTP) was introduced by the Malaysia's Prime Minister Dato' Sri Najib Tun Razak in April 2009 and will continuously be led by the Prime Minister himself in an effort to transform the Government to improve its delivery of services to the people and move Malaysia forward to achieve the aspirations of Vision 2020. The GTP Roadmap, which is launched on 28 January 2010, describes the details of the GTP on how its work. The GTP embodies the principles of 1 Malaysia, People First, Performance Now. The GTP and delivery in the National Key Result Areas (NKRA) will improve the lives of all Malaysians irrespective of race, religion and region. It is also helping people to achieve the ideals of 1 Malaysia. In developing the GTP and selecting the National Key Result Areas NKRAs, they put the people's priorities first and will continuously seek feedback to improve this programmed from the people itself. Which mean people first and to ensure Performance Now. They have put in place mechanisms to give them higher confidence of delivery and also this includes the publication of the GTP Roadmap and future Annual Reports which will detail the progress made against each target, Key Performance Indicator (KPIs) for ministers along with six-monthly reviews with the Prime Minister, pro-active feedback from the people via Open Days and many more. Besides that, they are also working in highly intensive cross agency labs and establish the Performance Management and Delivery Unit (PEMANDU). Economic Transformation Programme (ETP) launched on September 21, 2010, which focuses to turn Malaysia into a high-income nation by the year 2020. It is managed by the Performance Management and Delivery Unit (PEMANDU), an agency under the Prime Minister Department of Malaysia.